Quand des agriculteurs agroforestiers haut-garonnais nous parlent d’arbre et de paysage - Olivier Bories; Mathilde Rue (Projets de Paysage)
The article presents the main findings of a research study conducted in 2015 on the role of the landscape in the agroforestry commitment of ten farmers in the Haute Garonne region in France, based on the premise that the potential of the agroforestry landscape is a factor in such a commitment. Our research investigated the farmers’ positions regarding the landscape. The profiles of the farmers were studied first : Who are they ? What is their life trajectory and background ? The research then focused on their social representations to understand the motivations behind the practice of planting trees in or on the edges of plots. Gert, François, Roger, Arnaux and the other forest farmers we interviewed talked to us about agroforestry and the landscape. This enabled us to identify their positions concerning the landscape which were explained and described, for example regarding the intention to build a beautiful landscape or the desire to change the landscape in order to leave a mark on it.